Identification, production and assessment of two Toxoplasma gondii recombinant proteins for use in a Toxoplasma IgG avidity assay. (16th November 2016) - Teh, Ai Ying; Amerizadeh, Atefeh; Osman, Sabariah; Yunus, Muhammad Hafiznur; Noordin, Rahmah
Abstract : The IgG avidity assay is an important tool in the management of suspected toxoplasmosis in pregnant women. This study aimed to produce new Toxoplasma gondii recombinant proteins and to assess their usefulness in an IgG avidity assay. Toxoplasma positive and negative serum samples were used, the former were categorized into low (LGA) and high (HGA) IgG avidity samples. Immunoblots were performed on 30 T. gondii cDNA clones to determine the reactivity and IgG avidity to the expressed proteins. Two of the clones were found to have diagnostic potential and were analyzed further; AG12b encoded T. gondii apical complex lysine methyltransferase (AKMT) protein and AG18 encoded T. gondii forkhead-associated (FHA) domain-containing protein. The His-tagged recombinant proteins, rAG12b and rAG18, were expressed and tested with LGA and HGA samples using an IgG avidity western blot and ELISA. With the IgG avidity western blot, rAG12b identified 86.4% of LGA and 90.9% of HGA samples, whereas rAG18 identified 81.8% of both LGA and HGA samples. With the IgG avidity ELISA, rAG12b identified 86.4% of both LGA and HGA samples, whereas rAG18 identified 77.3% of LGA and 86.4% of HGA serum samples. This study showed that the recombinant antigens were able to differentiate low avidity and high avidity serum samples, suggesting that they are potential candidates for use in the Toxoplasma IgG avidity assay.